2010
DOI: 10.1371/journal.pone.0010008
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus Stimulates the NLRP3 Inflammasome through a Pathway Requiring ROS Production and the Syk Tyrosine Kinase

Abstract: Invasive aspergillosis (IA) is a life-threatening disease that occurs in immunodepressed patients when infected with Aspergillus fumigatus. This fungus is the second most-common causative agent of fungal disease after Candida albicans. Nevertheless, much remains to be learned about the mechanisms by which A. fulmigatus activates the innate immune system. We investigated the inflammatory response to conidia and hyphae of A. fumigatus and specifically, their capacity to trigger activation of an inflammasome. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
231
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(253 citation statements)
references
References 44 publications
15
231
1
6
Order By: Relevance
“…2C) is in accordance to the role of this receptor in the response against other fungal pathogens, as Candida albicans, 11 Aspergillus fumigatus, 16 Paracoccidioides brasiliensis 19 and dermatophytes as Trichophyton schoenleinii 18 and Microsporum canis. 17 However, the works on dermatophytes focused mainly on THP-1 monocytes, which show a constitutive caspase-1 activity and rely on pro-IL-1b transcription/expression as the limiting step for IL-1b production, while BMDMs obey to a 2-signal model to activate inflammasomes: signal 1, TLR activation for transcription; and signal 2, NLR activation for inflammasome assemblage.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…2C) is in accordance to the role of this receptor in the response against other fungal pathogens, as Candida albicans, 11 Aspergillus fumigatus, 16 Paracoccidioides brasiliensis 19 and dermatophytes as Trichophyton schoenleinii 18 and Microsporum canis. 17 However, the works on dermatophytes focused mainly on THP-1 monocytes, which show a constitutive caspase-1 activity and rely on pro-IL-1b transcription/expression as the limiting step for IL-1b production, while BMDMs obey to a 2-signal model to activate inflammasomes: signal 1, TLR activation for transcription; and signal 2, NLR activation for inflammasome assemblage.…”
Section: Discussionsupporting
confidence: 69%
“…IL-1b production relies on NLRP3, ASC and Caspase-1 Since the most studied inflammasome associated to fungal infections is the NLRP3, 11,[16][17][18][19] we sought to investigate whether this molecule could be necessary in our system. By analyzing the interaction between NLRP3 ¡/¡ BMDMs and T.rubrum conidia, we observed that the lack of this receptor did not change the interaction outcome ( Fig.…”
Section: Trubrum Conidia Induces Il-1b Production In Bmdmsmentioning
confidence: 99%
“…NLRP3 responds to multiple stimuli and forms an intracellular multiprotein complex, called NLRP3 inflammasome, consisting of the apoptosisassociated speck-like protein containing a caspase recruitment domain, and caspase-1, which triggers the secretion of IL-1β [8]. A recent report by Kayagaki et al [9] demonstrated that caspase-11 is also involved in a noncanonical inflammasome activation.NLRP3 inflammasome is activated in response to a range of bacterial, viral, and fungal pathogens, including Aspergillus fumigatus and C. albicans [10][11][12]. IL-1β production via the inflammasome generally requires two signals: an NF-κB-dependent signal that induces the synthesis of pro-IL-1β, and a second signal that triggers proteolytic pro-IL-1β processing to produce mature IL-1β.…”
mentioning
confidence: 99%
“…NLRP3 inflammasome is activated in response to a range of bacterial, viral, and fungal pathogens, including Aspergillus fumigatus and C. albicans [10][11][12]. IL-1β production via the inflammasome generally requires two signals: an NF-κB-dependent signal that induces the synthesis of pro-IL-1β, and a second signal that triggers proteolytic pro-IL-1β processing to produce mature IL-1β.…”
mentioning
confidence: 99%
“…The activation of caspase-1 is largely mediated by a cellular complex called inflammasome, which contains cytoplasmic PRRs such as NLRP3, NLRC4 or AIM2, adaptor protein ASC in most cases and pro-caspase-1 [4]. As IL-1β production via the NLRP3 inflammasome has been proved to be essential in host defense against pathogenic Candida albicans and Aspergillus fumigatus infections, and IL-1β production was detected from C. neoformansinfected mice [5][6][7], we hypothesized that C. neoformans can also activate the NLRP3 inflammasome and the latter is important for the control of C. neoformans infection. Indeed, in the present study, we found that biofilm from a clinical strain of C. neoformans induced robust IL-1β production from both human monocytes and murine dendritic cells in a NLRP3-dependent manner, and the NLRP3 inflammasome was essential for protection against C. neoformans infection.…”
mentioning
confidence: 99%